Incremental net benefit of whole genome sequencing for newborns and children with suspected genetic disorders: Systematic review and meta-analysis of cost-effectiveness evidence. Issue 4 (April 2022) - Nurchis, Mario Cesare; Riccardi, Maria Teresa; Radio, Francesca Clementina; Chillemi, Giovanni; Bertini, Enrico Silvio; Tartaglia, Marco; Cicchetti, Americo; Dallapiccola, Bruno; Damiani, Gianfranco
Abstract: Background: The introduction of massive parallel sequencing has contributed to a decline in sequencing costs. In recent years, whole-exome sequencing (WES) and whole-genome sequencing (WGS) have been increasingly adopted for diagnostic purposes in individuals with suspected genetic diseases. However, a debate is still ongoing in the scientific community about the superiority of WGS over WES in terms of cost-effectiveness. The aim of this study is to assess whether WGS, for the pediatric population with suspected genetic disorders, is cost-effective with respect to WES and chromosomal microarray (CMA) by pooling incremental net benefits. Materials and methods: Articles were retrieved from PubMed, Web of Science, Embase and Scopus from 2015 to 2021. The dominance ranking matrix (DRM) tool was adopted to provide a qualitative synthesis of all the included studies. Incremental net benefits (INBs) were estimated and meta-analysis was implemented to pool INBs across studies. Results: The database search identified 1600 publications of which four articles were considered eligible for the meta-analysis. The pooled INB of WGS over WES was estimated at I$4073 (95% CI I$2426 – I$5720). The pooled INB of WGS over CMA amounted to I$6003 (95% CI I$2863 – I$9143). Conclusions: WGS could be cost-effective in the diagnostic workup of affected infants and children. Further economic evaluations however are needed for comparing WGS versus WES and confirm the present conclusions. Highlights: WGS could be cost-effective in diagnostic workup of affected infants and children. First-tier WGS could bend the cost trajectory of the diagnostic care pathway. Adoption of proper tools and methodologies to formulate evidence-based health policies.